2009
DOI: 10.1158/0008-5472.can-09-1161
|View full text |Cite|
|
Sign up to set email alerts
|

Zerumbone Enhances TRAIL-Induced Apoptosis through the Induction of Death Receptors in Human Colon Cancer Cells: Evidence for an Essential Role of Reactive Oxygen Species

Abstract: Identification of the active component and mechanisms of action of traditional medicines is highly desirable. We investigated whether zerumbone, a sesquiterpene from tropical ginger, can enhance the anticancer effects of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). We found that zerumbone potentiated TRAIL-induced apoptosis in human HCT116 colon cancer cells and that this correlated with the up-regulation of TRAIL death receptor (DR) 4 and DR5. Induction of DRs occurred at the transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
141
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(160 citation statements)
references
References 44 publications
18
141
1
Order By: Relevance
“…Moreover, we noticed that the knockdown of DR5 and DR4 by their respective siRNAs effectively inhibited the cell death induced by the combination of emodin and TRAIL, demonstrating the pivotal role of death receptors in the apoptotic process (data not shown). These results are consistent to a previous reported in which another chemopreventive agent, zerumbone was found to enhance TRAIL-induced apoptosis through induction of death receptors in colorectal cancer cells [41]. Our results are also partially in agreement with another study by Kim and coworkers who have previously reported that the inhibition of casein kinase 2 by emodin can sensitize HCC cells to both Fas ligand-and TRAIL-induced apoptosis and also increased the NK cell-mediated tumor cell killing [42].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, we noticed that the knockdown of DR5 and DR4 by their respective siRNAs effectively inhibited the cell death induced by the combination of emodin and TRAIL, demonstrating the pivotal role of death receptors in the apoptotic process (data not shown). These results are consistent to a previous reported in which another chemopreventive agent, zerumbone was found to enhance TRAIL-induced apoptosis through induction of death receptors in colorectal cancer cells [41]. Our results are also partially in agreement with another study by Kim and coworkers who have previously reported that the inhibition of casein kinase 2 by emodin can sensitize HCC cells to both Fas ligand-and TRAIL-induced apoptosis and also increased the NK cell-mediated tumor cell killing [42].…”
Section: Discussionsupporting
confidence: 94%
“…Zerumbone has been reported to enhance TRAILinduced apoptosis through ROS-mediated induction of DR5 [43]. Our findings also demonstrated that combined treatment with acrolein and TRAIL increased ROS levels in Caki cells and antioxidant (NAC) pretreatment prevented ROS generation and this apoptosis induced by acrolein plus TRAIL (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…However, shogaols have gained more interest because of recent discoveries revealing their higher anti-cancer potencies over gingerols (Sang et al, 2009). Another component in ginger extract, zerumbone, a sesquiterpene in ginger, has been suggested to induce apoptosis in HCT 116 cell line as indicated by upregulation of tumor necrosis factor-related apoptosisinducing ligand (TRAIL) death receptor (DR) 4 and DR5 (Yodkeeree et al, 2009) while 6-shogaol has been suggested to induce apoptosis in colon adenocarcinoma cell line COLO 205 (Pan et al, 2008). Nevertheless in this study crude ginger extract was used instead of either individual gingerol or shogaol as there is recent evidence suggesting combination of active compounds present in ginger could synergistically enhance the anti-cancer effect of ginger (Brahmbhatt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%